Sustainability of the Philippine food system - Golloso-Gubat, Maria Julia; Felix, Angelina dR; Tandang, Nancy A.; Acuin, Cecilia Cristina S.; Gordoncillo, Prudenciano U.; Duante, Charmaine A. (Frontiers in Sustainable Food Systems, 2024)
Understanding the Philippine food system status is vital in identifying pathways to improve sustainable nutrition security in the country. In the present study, we quantitatively examined the sustainability status of the Philippine food system using the Sustainable Nutrition Security (SNS) metrics. The country’s food system obtained the low scores for Resilience, Food Nutrient Adequacy, Ecosystem Stability, and Food Safety; while better scores were obtained for Sociocultural Wellbeing, Food Affordability and Availability, and Waste and Loss Reduction. The Philippine food production and supply faces important challenges on diversification, coupled with socioeconomic disparities. Potential convergence points among relevant stakeholders were identified to improve the diversity of the food supply chain and to develop the overall resilience of the Philippine food system.